Validating the whistleblowing maturity model using the delphi method - Paschalis Kagias; Nikolaos Sariannidis; Alexandros Garefalakis; Ioannis Passas; Panagiotis Kyriakogkonas (Administrative Sciences, 2023)
Empirical research identifies whistleblowing as one of the most effective internal antifraud controls. Very recently, Directive 1937/2019 became effective in the EU, aiming to deal with the defragmentation of whistleblowing legislation among the member states and provide common minimum accepted standards. The present article aims to provide a verified, weighted comparative maturity model. The suggested model has been constructed based on the methodology for constructing comparative maturity models and validated based on the Delphi method. The weights on each validated component have been calculated based on the summing of votes method. The study resulted in eight main components "scope", "corporate governance", "reporting mechanisms", "protection", "tone at the top", "organizational and human resource practices", "investigations" and "monitor and review" divided further into 18 elements. The suggested maturity model may provide a pathway for organizations to develop and maintain a robust whistleblowing maturity framework that will benefit both the organizations and the public welfare.
Keywords: 350; benchmarking; ESG; EU Directive 1937; internal audit; whistleblowing